Language Errors in the Thesis Title of Arabic Education Students - Mukroji, Mukroji; Jamil, Shobrun; Taufiq, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2022)
One of the main problems in language acquisition is the grammatical mastery of either nahwu or sharaf, as has happened in several cases, both in formal and non-formal educational institutions. The purpose of this paper was to find language errors in the students' thesis of Arabic Language Education Study Program which was prepared by using Arabic in UIN Prof. K.H. Saifuddin Zuhri Purwokerto. Content analysis and language error analysis based on Language Theory was used in this research that lied by Miles and Huberman. The study found that there were several forms of language errors in the morphology and syntax. Morphology is an error in grammatical arrangement. There were structure of idafiyah or compound words errors in 9 titles or 50%. Afterwards, Na’atman'ut and hal were found in 3 titles or 20%. Meanwhile, the semantics errors found that related to the use of standard words in 6 titles or 30% and the rest was related to inaccurate word choice or diction. Syntax errors in Arabic writing are very common. It has implications for several things, such as professionalism or the ability to master one form of expertise in Arabic other than qira'ah or kitabah.